2021
DOI: 10.23969/sampurasun.v7i2.4635
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Challenges in Virtual Classroom to Maintain Effective Classroom Management and Classroom Culture: A Case Study at One Vocational School

Abstract: Effective classroom management supports the teacher classroom teaching profoundly. During Pandemic COVID 19 most classroom teachings are conducted in virtual classroom that have been greatly affected the way how teacher manage his or her own classroom. This causes some challenges for teachers in managing his or her virtual classroom. This study was conducted in the form of a case study in one vocational school in West Bandung region, West Java, Indonesia in which one English teacher was purposively selected as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Therefore, it is needed for a lecturer to have better class management and prepare everything needed for teaching online through Zoom Cloud Meeting. This is also supported by a previous study by Mardiani & Azhar (2021) The last challenge in the content presentation stage is a lack of time or poor time management. When lecturers explain the material, they sometimes explain it a little outside the allotted time.…”
Section: Herdiansyah a And Fajriah Y N Lecturers' Challenges In Teach...supporting
confidence: 82%
“…Therefore, it is needed for a lecturer to have better class management and prepare everything needed for teaching online through Zoom Cloud Meeting. This is also supported by a previous study by Mardiani & Azhar (2021) The last challenge in the content presentation stage is a lack of time or poor time management. When lecturers explain the material, they sometimes explain it a little outside the allotted time.…”
Section: Herdiansyah a And Fajriah Y N Lecturers' Challenges In Teach...supporting
confidence: 82%
“…This finding aligns with previous research on classroom management. Mardiani and Azhar (2021) demonstrated that effective classroom management ensures successful teaching by instructors. Additionally, Wilkinson et al (2020) emphasised the crucial role of teachers' classroom management abilities in fostering high-quality educational outcomes for students.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, virtual classroom has some advantages, such as the students have ability to explore a lot of information in the internet about their lesson; therefore, the students can learn independently. Besides, the students can utilize the facilities from internet to help their activities, such as google calendar to remind them about their to do list, emails to help them sending their task to the teachers everywhere and every time, and chat room DOI 10.18502/kss.v8i10.13432 to help the students asking if they have questions, but they are too shy to ask by oral communication (Mardiani & Azhar, 2021). However, even though virtual classroom can provide some materials easily for students and also teachers, but it still has some challenges for the teachers to manage the classroom.…”
Section: Introductionmentioning
confidence: 99%